2006
DOI: 10.1007/s10546-006-9137-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of secondary circulations over an inhomogeneous surface simulated with large-eddy simulation

Abstract: Large-eddy simulation is used to study secondary circulations in the convective boundary layer modulated as a result of horizontally varying surface properties and surface heat fluxes over flat terrain. The presence of heat flux heterogeneity and its alignment with respect to geostrophic wind influences the formation, strength and orientation of organized thermals. Results show boundary-attached roll formation along heat flux maxima in the streamwise direction. The streamwise organization of the updrafts and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
6
29
0
Order By: Relevance
“…Furthermore, we find a spread in the development of cloud streets depending on the magnitude of the prescribed Q net , with correlation ratios ranging from 1 to 5. The fact that buoyancy-driven cloud street organization is favored in slightly unstable conditions (low sun) compared to stronger instabilities (high sun) agrees well with observations (e.g., Woodcock, 1942;Priestley, 1957;Grossman, 1982;Weckwerth et al, 1997).…”
Section: Without Wind: U = 0 M S −1supporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we find a spread in the development of cloud streets depending on the magnitude of the prescribed Q net , with correlation ratios ranging from 1 to 5. The fact that buoyancy-driven cloud street organization is favored in slightly unstable conditions (low sun) compared to stronger instabilities (high sun) agrees well with observations (e.g., Woodcock, 1942;Priestley, 1957;Grossman, 1982;Weckwerth et al, 1997).…”
Section: Without Wind: U = 0 M S −1supporting
confidence: 89%
“…Moving forward, we will examine whether the relationship between radiative transfer and convective cloud streets also applies to the real world with all the complexities of a diurnal cycle or static surface heterogeneities combined with complex wind fields. Several studies perform detailed analyses on the footprint of static surface heterogeneities in windy conditions, i.e., how upstream heterogeneities influence the characteristics of boundary layer dynamics (e.g., Raasch and Harbusch, 2001;Prabha et al, 2007;Courault et al, 2007;Maronga and Raasch, 2013;Chen et al, 2015;Gronemeier et al, 2016). It may very well be worth revisiting their analyses and particularly focus on static and dynamic (radiative) heterogeneities.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason for this disagreement may arise from the different heterogeneity alignments with respect to wind directions used in those studies. Prabha et al (2007) showed that the heat flux heterogeneity and its alignment with respect to geostrophic wind affected the strength and orientation of organized thermals, and similar results were obtained by Kim et al (2004).…”
Section: Introductionsupporting
confidence: 72%
“…Land surface heterogeneities with different spatial scales also have different effects on the CBL; land surface heterogeneities at scales of tens of kilometres can induce mesoscale circulations (Gopalakrishnan et al, 2000;Baidya Roy et al, 2003;Kustas and Albertson, 2003;Kang et al, 2007;Taylor et al, 2007;Garcia-Carreras et al, 2010) while heterogeneities with scales (λ) on the order of the boundary-layer height (Z i ) mainly influence various CBL properties depending on values of λ/Z i (Prabha et al, 2007; and the references therein). Baidya showed that meso-γ -scale (2 ∼ 20 km) surface heterogeneity produces organized circulations with the same horizontal length-scale as that of the heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed by Prabha et al (2007), the orientation of surface heterogeneity with respect to the geostrophic wind is important. Stationary circulations may develop, which can enhance entrainment and down-wind scalar diffusion.…”
Section: Introductionmentioning
confidence: 99%